2018
DOI: 10.2478/rrlm-2018-0023
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic variations in Candida albicans isolates from Romanian patients

Abstract: Background: During the last two decades a major increase in the proportion of severe fungal infections has been noted due to the excessive use of broad-spectrum antibiotics, catheters, and a growing number of immunocompromised patients. Objectives: This is the first investigation providing complete data regarding the phenotypic and genotypic profiles of Candida albicans (C. albicans) isolates in Romanian patients. Methods: We investigated 301 isolates in terms of genotype determination (G), resistogram (R), ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…albicans isolates. In a study with diverse clinical samples, Rosca et al 27 found no significant correlation between genotype (A at 52.92%, B at 17.85%, C at 29.20%) and the infection site. It thus appears that genotype A is the most frequent genotype in clinical specimens.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…albicans isolates. In a study with diverse clinical samples, Rosca et al 27 found no significant correlation between genotype (A at 52.92%, B at 17.85%, C at 29.20%) and the infection site. It thus appears that genotype A is the most frequent genotype in clinical specimens.…”
Section: Discussionmentioning
confidence: 96%
“…albicans is divided into several genotypes based on the electrophoresis banding pattern, for example, A, B, C, D, and E. 24 , 25 In oral, vulvovaginal, and nail samples, the A genotype was the predominant type in previous studies. 26 , 27 , 28 …”
Section: Introductionmentioning
confidence: 99%
“…The current study revealed that genotype A had the highest prevalence among the isolated C. albicans (52.3%), followed by genotype B (31.8%) and the least was genotype C (15.9%). Several studies have reported similar results like Takakura et al 22 and Da Matta et al 23 However, Sardi et al 24 found the most prevalent genotype was B and did not report any isolates of genotype C. The second prevalent genotype after A was C in study conducted by Rosca et al 25 …”
Section: Discussionmentioning
confidence: 62%
“…For example, further correlations between genotypes and pathogenicity factors are bringing more evidence on the interrelation between host and microorganism. An epidemiological study published on this issue follows these factors that contribute to the pathogenic potential of C. albicans (6), and it was found that the levels of enzymatic activity of C. albicans is a strain-dependent variable, and that not all strains were capable to produce biofilm. Such details are important to be considered when dealing with Candida infections, remembering that even if the identified species is the same from different patients/samples, they can also be totally different in terms of pathogenicity and chemo-resistance.…”
Section: Editorialmentioning
confidence: 99%